Insight On Colorectal Carcinoma Infiltration by Studying Perilesional Extracellular Matrix - Nebuloni, Manuela (Sci Rep, 2016)
The extracellular matrix (ECM) from perilesional and colorectal carcinoma (CRC), but not healthy colon, sustains proliferation and invasion of tumor cells. We investigated the biochemical and physical diversity of ECM in pair-wised comparisons of healthy, perilesional and CRC specimens. Progressive linearization and degree of organization of fibrils was observed from healthy to perilesional and CRC ECM, and was associated with a steady increase of stiffness and collagen crosslinking. In the perilesional ECM these modifications coincided with increased vascularization, whereas in the neoplastic ECM they were associated with altered modulation of matrisome proteins, increased content of hydroxylated lysine and lysyl oxidase. This study identifies the increased stiffness and crosslinking of the perilesional ECM predisposing an environment suitable for CRC invasion as a phenomenon associated with vascularization. The increased stiffness of colon areas may represent a new predictive marker of desmoplastic region predisposing to invasion, thus offering new potential application for monitoring adenoma with invasive potential.